Smallpox in turkeys - Safarova Zakiya; Gaziyeva Gulandom (E3S Web of Conferences, 2023)
The article describes epidemiological diseases of animals, in particular smallpox of birds. The disease of turkeys, such as turkey pox, its spread, transmission, signs and treatments are revealed. In our country, animals are mostly bred in rural areas. The quality and ecological purity of their products is better than that of products grown in specialized farms and poultry farms. Since, in rural areas, local and traditional methods are used to treat livestock and poultry. Although the level of exposure to chemicals is high, it is not always recommended to use them, in rural areas much attention is paid to ensuring environmental cleanliness of products. Therefore, in our scientific observations, research and experiments, we also used environmentally friendly methods that are widely used by the rural population, and our results satisfied us from a practical and scientific point of view. We have conducted scientific studies of smallpox in birds – one of the epidemiological diseases that occur in poultry in the autumn-spring period. Experiments were conducted on turkeys and their turkeys, in particular chicken. During the experiment and scientific research, the speed of the spread of the disease, its individuality, resistance to chemical and natural agents were observed. In the treatment of smallpox of birds, in addition to chemicals, crushed fresh leaves and stems of plantain lanceolate (Plantago lanceolata), shepherd's bags (Capsélla bursa-pastóris), alfalfa plants (Medicago sativa) were widely used. The use of green plant masses positively affected the appetite of turkeys, satisfying their need for vitamins C, K, and antioxidants.